Design of a combined apparatus for low-temperature processing of confectionery products based on plant-based multicomponent semi-finished products - Zahorulko, Andrii; Voronenko, Iryna; Nikolaienko, Mykola; Minenko, Sofiia; Ponomarenko, Nataliia; Zakharchenko, Ruslan; Ibaiev , Eldar; Tytarenko, Nataliia (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of low-temperature processing of confectionery products, in particular marshmallows made on the basis of plant polycomponent semi-finished products, taking into account the parameters of infrared heating and preliminary air preparation. The task relates to the lack of effective technologies for low-temperature processing of confectionery products with plant polycomponent semi-finished products to preserve their quality and functionality. A model of a combined apparatus for low-temperature processing of confectionery products, in particular marshmallows made on the basis of plant polycomponent semi-finished products, is given. The apparatus has a rectangular chamber with rounded edges for uniform heat flow, a film-like resistive electric heater of the radiant type (30…120°C), replaceable functional trays, and an autonomous ventilation system based on Peltier elements. Air is recirculated with preliminary drying and heating up to 45°C. The uniformity of the heat flux distribution on the receiving surface has been confirmed: the central temperature was 46.0°C, the contour temperature was within 42.0…43.1°C. This thermal regime helps stabilize the structure of confectionery products during low-temperature processing. The experimental process of drying marshmallows demonstrates effective dehydration: classic marshmallows lose up to 20% of moisture in 50 min, marshmallows with plant polycomponent semi-finished products – up to 22% in 70 min, and marshmallows with plant polycomponent semi-finished products and amaranth – up to 24% in 80 min. The data indicate the need to extend the drying time of samples with plant ingredients because of their increased hydrophilicity. Sensory evaluation has confirmed the high quality of the finished confectionery products. The highest indicators were obtained for marshmallows with RPN and amaranth (aroma – 5.0; taste – 4.9; structure – 4.8). The designed structure became the basis for assembling a device with high-quality low-temperature processing of confectionery products. The device is suitable for the production of pastilles, snacks, bakery products, and drying of plant raw materials in pharmaceuticals and cosmetics